Lightweight UDP Pervasive Protocol in Smart Home Environment Based on Labview - Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan; Sabriansyah Rizqika Akbar; Issa Arwani (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
TCP (Transmission Control Protocol) technology in a reliable environment was not a problem, but not in an environment where the entire Smart Home network connected locally. Currently employing pervasive protocols using TCP technology, when data transmission  is sent, it would be slower because they have to perform handshaking process in advance and could not broadcast the data. On smart home environment, it does not need large size and complex data transmission between monitoring site and monitoring center required in Smart home strain monitoring system. UDP (User Datagram Protocol) technology is quick and simple on data transmission process. UDP can broadcast messages because the UDP did not require handshaking and with more efficient memory usage. LabVIEW is a programming language software for processing and visualization of data in the field of data acquisition. This paper proposes to examine Pervasive UDP protocol implementations in smart home environment based on LabVIEW. UDP coded in LabVIEW and experiments were performed on a PC and can work properly.